2016
DOI: 10.3389/fpls.2016.01397
|View full text |Cite
|
Sign up to set email alerts
|

Does White Clover (Trifolium repens) Abundance in Temperate Pastures Determine Sitona obsoletus (Coleoptera: Curculionidae) Larval Populations?

Abstract: To determine if host plant abundance determined the size of clover root weevil (CRW) Sitona obsoletus larval populations, a study was conducted over 4 years in plots sown in ryegrass (Lolium perenne) (cv. Nui) sown at either 6 or 30 kg/ha and white clover (Trifolium repens) sown at a uniform rate of 8 kg/ha. This provided a range of % white clover content to investigate CRW population establishment and impacts on white clover survival. Larval sampling was carried out in spring (October) when larval densities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…By October 2012, clover root weevil densities had increased (consistent with overwintering recruitment of larvae), with greater populations in the 6 kg/ha treatment compared with the 30 kg/ha treatment ( p < .001; 430 vs. 189 larvae per m 2 respectively). Subsequent sampling in autumn 2014 and 2015 and early winter 2016 indicated that clover root weevil larval populations had declined to below damaging levels (McNeill, van Koten, Cave, Chapman, & Hodgson, ). By early winter 2016, grass grub densities were generally high (154 ± 190.3 across all sampled subplots), reaching damaging levels in a number of subplots.…”
Section: Resultsmentioning
confidence: 99%
“…By October 2012, clover root weevil densities had increased (consistent with overwintering recruitment of larvae), with greater populations in the 6 kg/ha treatment compared with the 30 kg/ha treatment ( p < .001; 430 vs. 189 larvae per m 2 respectively). Subsequent sampling in autumn 2014 and 2015 and early winter 2016 indicated that clover root weevil larval populations had declined to below damaging levels (McNeill, van Koten, Cave, Chapman, & Hodgson, ). By early winter 2016, grass grub densities were generally high (154 ± 190.3 across all sampled subplots), reaching damaging levels in a number of subplots.…”
Section: Resultsmentioning
confidence: 99%